(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Nutritional deficiencies remain a major public health concern, especially in rural and economically disadvantaged regions of India. Vijayanagara district in Karnataka, known for its rich cultural heritage, also faces significant challenges in terms of public health and nutrition. Malnutrition and specific micronutrient deficiencies like anemia, vitamin deficiencies, and protein-energy malnutrition are prevalent in this region, influenced by factors such as poverty, agricultural practices, dietary habits, and access to healthcare. Understanding the geographical distribution of these deficiencies is crucial to implementing targeted interventions that can improve the nutritional status of the population.